Mathematical Anxiety in Optimizing Students' Mathematical Problem-solving on the Plane Geometry Topic - Khairunnisa, Rohmatul Aulia; Hikmah, Zia Nurul; Nuriadin, Ishaq (Universitas PGRI Madiun, 2020)
This study aims to describe mathematical anxiety in solving students' mathematical problems. This type of research is qualitative research with a case study method. The subjects in this study consisted of 1 student who had a high level of anxiety. The technique of taking the subject is by using a purposive sampling technique. Data collection techniques using questionnaires, tests, and interviews. The instruments used were mathematical anxiety questionnaires, tests of mathematical problem-solving abilities, and interviews. The result shows that the subject has difficulty solving mathematical problems. It shows that the subject with high anxiety is not optimal in solving mathematical problem-solving problems. Thus, students with high anxiety need specific treatments or require the application of fun learning to optimize their mathematical problem-solving abilities